Analisis Penerapan Prinsip Good Corporate Governance Pada Prosedur Pemotongan PPH Pasal 21 Atas Penghasilan Pegawai Di Perum Pnri Pusat Tahun 2021 - Alfalah Irfaq; Notika Rahmi (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The application of the principles of good corporate governance is very important in a State-Owned Enterprise (BUMN) and it is stated in the Decree of the Minister of BUMN No. Kep-117/M-MBU/2002 concerning the implementation of good corporate governance practices in State-Owned Enterprises. The principle of good corporate governance aims to improve corporate governance while still paying attention to the interests of stakeholders, where taxation is a part of the company that must be managed properly, and one of the interests of the stakeholders is employee tax. The purpose of this study is to analyze the application of the principles of good corporate governance in the implementation of the employee tax policy at the Perum PNRI Pusat, the obstacles that affect the application of the principles of good corporate governance in the implementation of the tax policies for the employees at the Perum PNRI Pusat, and the efforts that must be made to overcome these obstacles. The research method used was descriptive qualitative method. The data used included primary data which was interview and observation data and secondary data obtained from company documents. The results of this study indicate that Perum PNRI has implemented the principles of good corporate governance well, which include transparency, accountability, responsibility, independence, and fairness. This has been stated in the Self-Assessment of Good Corporate Governance report of Perum PNRI, although there are still some aspects that need to be improved in its implementation.